Combined leadless pacing and subcutaneous defibrillation strategy in a high-risk patient: first case report from Peru - Vallejos-Barrientos, Alexis (2025)
We present the case of a 51-year-old male with non-ischemic dilated cardiomyopathy and complete atrioventricular block, who was previously implanted with a cardiac resynchronization therapy defibrillator. The patient developed signs of pocket infection with a high risk of extrusion. Partial system extraction was performed, followed by 14 days of intravenous antibiotic therapy. Due to a history of ventricular fibrillation and permanent pacing dependency, and in the absence of viable transvenous access, a sequential implantation strategy was adopted using a leadless pacemaker (Micra AV, Medtronic) and a subcutaneous implantable cardioverter-defibrillator (EMBLEM, Boston Scientific). Both procedures were completed without complications, and the patient showed favorable recovery, with effective pacing, no arrhythmic recurrences, and no signs of infection at the six-month follow-up. This case illustrates the feasibility of a fully leadless approach in high-risk patients with contraindications to conventional transvenous systems.